Estimating the Benefits of Beach Recreation: An Application of the Contingent Valuation Method - R. Abdullah, Nik Mustapha (Universiti Putra Malaysia Press, 1995)
This study presents an application of the dichotomous choice contingent valuation method to estimate the benefits of beach recreation in Port Dickson. The logit and probit models were used to analyse the data and the willingness-to-pay values were computed from the maximum likelihood estimates. The median willingnessto- pay value for beach recreation in Port Dickson ranged from RM55.01 to RM534.80 for mean income of RM404.56 to RM3933.30, respectively. These values can be used by policy-makers to compute the annual total benefits obtainable from this multiple-use resource.